An analysis of issues in biometric finger identification - Veerasamy, Nanda Kumar (International Journal of Engineering and Technology, 2014)
A Person's identity is an essential factor in this vastly connected society. Biometric Finger has wide acceptance as a genuine method for determining an individual’s identity. Biometric Finger authentication is reliable, since physical characteristics in humans are difficult to forge, harder to change or make copies. Biometric fingerprinting is one of the most popular and legally accepted biometrics used in person identification. Finger print authentication applications include Computer Applications, Network Access, Data Protection, Transaction Security, and Web Security. E-commerce and E-governments can carry out strong authentication rules. This paper analyzes issues related to Fingerprint identification to suggest viable alternatives. Keywords: Fingerprint Identification, Optical Sensors, Ultrasound Sensors, Issues in Finger Print Identification.